Inspecting teammates' coverage during attacking plays in a football game : a case study - Manuel Clemente, Filipe; M. L. Martins, Fernando; Couceiro, Micael; Mendes, Rui; Figueiredo, António J. ([Cardiff Metropolitan University], 2014)
The tactical behaviour of football players is fundamental in sport teams. Despite this importance, the methods to measure such behaviour are very time-consuming for human operators. Therefore, the aim of this case study was to propose a set of collective technological metrics to evaluate the attacking coverage provided by teammates to the player in possession of the ball. For this case study data was collected from three official matches of the same professional team. Using the information about the Cartesian position of players in the field provided from a tracking method, it was possible to propose four different technological metrics and ratios: i) cover in support; ii) cover in vigilance; iii) attacking cover; and iv) depth mobility. Using those metrics it was possible to observe that on average the team observed use with higher regularity support in vigilance as well as depth mobility, thus suggesting a specific tactical behaviour. In summary, it was possible to apply all metrics to real data from three official matches, thus allowing a new technological method to improve the match analysis systems that use multiplayer tracking.
Keywords: Match analysis; tactics; metrics; football